Answer:
$777.60
Step-by-step explanation:
8/100 = 0.08
0.08 * 720 = 57.6
57.6 + 720 = 777.6
Answer:
There is a 30% decrese.
Step-by-step explanation:
Answer:
56.8
Step-by-step explanation:
4/5+56 =56.8
very sorry if this is wrong
Answer:
-20...........................
Answer:
Part 1) ![g(x)=-x^{2}](https://tex.z-dn.net/?f=g%28x%29%3D-x%5E%7B2%7D)
Part 2) ![g(x)=(x+3)^{2}](https://tex.z-dn.net/?f=g%28x%29%3D%28x%2B3%29%5E%7B2%7D)
Part 3) ![g(x)=x^{2}+7](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E%7B2%7D%2B7)
Step-by-step explanation:
we have
The parent function is ![f(x)=x^{2}](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E%7B2%7D)
This is a vertical parabola open upward with vertex at origin (0,0)
Part 1) Reflection over the x-axis
The rule of the reflection across the x=axis is equal to
(x,y) ------> (x,-y)
so
f(x) -----> g(x)
The function g(x) will be
![g(x)=-x^{2}](https://tex.z-dn.net/?f=g%28x%29%3D-x%5E%7B2%7D)
Part 2) Horizontal shift left 3 units
The rule of the translation is
(x,y) ------> (x-3,-y)
so
f(x) -----> g(x)
The function g(x) will be
![g(x)=(x+3)^{2}](https://tex.z-dn.net/?f=g%28x%29%3D%28x%2B3%29%5E%7B2%7D)
Part 3) Vertical shift up 7 units
The rule of the translation is
(x,y) ------> (x,y+7)
so
f(x) -----> g(x)
The function g(x) will be
![g(x)=x^{2}+7](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E%7B2%7D%2B7)